Geophysical assessment of aquifer protectivity, groundwater potential and flow dynamics in Northern Akwa Ibom state, Nigeria: Implications for sustainable freshwater management - Emem O. Ikpe; Aniekan M. Ekanem; Nyakno J. George; Jewel E. Thomas (Geosystems and Geoenvironment)
Sustainable fresh water supply constitutes one of the challenges in recent times. We present the results of the geophysical valuation of aquifer protectivity, groundwater potentiality and flow properties in the northern part of Akwa Ibom state, Nigeria. Vertical electrical sounding (VES) and electrical resistivity tomography (ERT) were conducted at 55 and 20 locations respectively in the study area to generate 1D and 2D resistivity sections of the subsurface. A maximum of four layers have been delineated from the results of the electrical resistivity soundings. These layers are successions of poorly–sorted sands and gravels with minor clay intercalation at some locations. The aquifers lie between 1.0 to 47.8 m deep and are 18.6 to 102.7 m thick. The aquifer protective capacity (APC) grading is adjudged to be poor (96 %) to weak (4 %) respectively as the overlying layers are mostly porous and permeable. However, the aquifers have great groundwater potential with 6 % moderate grading, 9 % high grading and 85 % very high grading. The discrete rock typing (DRT) results delineate the aquifers into two hydraulic flow units (HFU) of sandy clay and fine/coarse/gravelly sands. The stratigraphic modified Lorenz Plot (SMLP) technique however delineates the aquifers into five HFUs, classified as conductors (96 %) and super conductors (4 %) with ranking efficiencies of fair and good respectively. The DRT and SMLP classifications seem to show consistency, which indicate the fidelity of our investigation approach. The aquifer units are shown to be highly heterogeneous, corroborated by the electrical resistivity sounding results and the variability in the HFUs inferred from the SMLP results. The established regression equations in this research could be utilized for the predictions of aquifer hydraulic and flow properties from surficial electrical sounding data in locations with comparable geology. These results are highly propitious in the development of efficient strategies to preserve groundwater resources in the area by policymakers and water resource managers.